The Early Mesoamerican Village : (Updated Edition). - Flannery, Kent V. (Left Coast Press, 1976)
This is a seminal tract on scientific method in archaeology and a series of studies on formative Mesoamerica that has influenced generations of archaeologist. A new Foreword by Jeremy Sabloff is featured in this edition.